Clark M. Clifford papers - Clifford, Clark M., 1906-1998.
Correspondence, memoranda, speeches and writings, congressional testimony, printed matter, and other papers relating primarily to Clark M. Clifford's personal and professional life including his role as an adviser and counsel to the Democratic administrations of Harry S. Truman, John F. Kennedy, Lyndon B. Johnson, and Jimmy Carter; his service as U.S. secretary of defense (1968-1969); and his career as a lawyer in Washington, D.C.
Subjects include the relationship between business and government, politics, national security, international relations, law, presidential elections and transitions, the Truman Doctrine, the National Security Act, the Vietnam war, Clifford's mission to Cyprus in 1977, his involvement with the Bank of Credit and Commerce International, and his role as personal lawyer for John F. Kennedy.
Correspondents include Dean Acheson, Joseph Alsop, Clinton Presba Anderson, George W. Ball, Birch Bayh, Edmund G. Brown, Hillyard Brown, McGeorge Bundy, William P. Bundy, Jimmy Carter, Tom C. Clark, Barnum L. Colton, Donald C. Cook, James Cooke, Justin Whitlock Dart, Joseph Edward Davies, Thomas F. Eagleton, Dwight D. Eisenhower, Leonard K. Firestone, J. William Fulbright, Grace Halsell, W. Averell Harriman, William D. Hassett, Hubert H. Humphrey, Lyndon B. Johnson, John F. Kennedy, Robert F. Kennedy, John Shively Knight, Melvin R. Laird, Bert Lance, John H. Lashly, Paul W. Lashly, Charles McC. Mathias, David G. McCullough, George S. McGovern, Mary McGrory, Edward P. Morgan, Edmund S. Muskie, Jacqueline Kennedy Onassis, Paul Aldermandt Porter, Elwood R. Quesada, W. W. Rostow, James H. Rowe, Dean Rusk, George A. Smathers, Bess Wallace Truman, Harry S. Truman, James Jeremiah Wadsworth, Thomas J. Watson, and Edward Bennett Williams.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Lawyer and cabinet officer. Full name: Clark McAdam Clifford.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Alsop, Joseph, -- 1910-1989 -- Correspondence; Anderson, Clinton Presba, -- 1895- -- Correspondence; Ball, George W. -- Correspondence; Bayh, Birch, -- 1928- -- Correspondence; Brown, Edmund G. -- 1905-1996 -- Correspondence; Brown, Hillyard -- Correspondence; Bundy, McGeorge -- Correspondence; Bundy, William P., -- 1917- -- Correspondence; Carter, Jimmy, -- 1924-; Carter, Jimmy, -- 1924- -- Correspondence; Clark, Tom C. -- 1899-1977 -- Correspondence; Colton, Barnum L. -- Correspondence; Cook, Donald C. -- Correspondence; Cooke, James -- Correspondence; Dart, Justin Whitlock, -- 1907- -- Correspondence; Davies, Joseph Edward -- Correspondence; Eagleton, Thomas F., -- 1929-2007 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Firestone, Leonard K. -- 1907-1996 -- Correspondence; Fulbright, J. William -- 1905-1995 -- Correspondence; Halsell, Grace -- Correspondence; Harriman, W. Averell -- 1891-1986 -- Correspondence; Hassett, William D., -- 1880-1965 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963 -- Correspondence; Kennedy, Robert F., -- 1925-1968 -- Correspondence; Knight, John Shively, -- 1894-1981 -- Correspondence; Laird, Melvin R. -- Correspondence; Lance, Bert, -- 1931-2013 -- Correspondence; Lashly, John H. -- 1916-1987 -- Correspondence; Lashly, Paul W. -- 1917-; Mathias, Charles McC. -- 1922-2010 -- Correspondence; McCullough, David G. -- Correspondence; McGovern, George S. -- 1922-2012 -- Correspondence; McGrory, Mary, -- 1918- -- Correspondence; Morgan, Edward P., -- 1910-1993 -- Correspondence; Muskie, Edmund S., -- 1914-1996 -- Correspondence; Onassis, Jacqueline Kennedy, -- 1929-1994 -- Correspondence; Porter, Paul Aldermandt, -- 1904-1975 -- Correspondence; Quesada, Elwood R. -- 1904- -- Correspondence; Rostow, W. W. -- 1916-2003 -- Correspondence; Rowe, James H. -- 1909-1984 -- Correspondence; Rusk, Dean, -- 1909-1994 -- Correspondence; Smathers, George A. -- 1913-2007 -- Correspondence; Truman, Bess Wallace -- Correspondence; Truman, Harry S., -- 1884-1972.; Truman, Harry S., -- 1884-1972 -- Correspondence; Wadsworth, James Jeremiah, -- 1905- -- Correspondence; Watson, Thomas J., -- 1914-1993 -- Correspondence; Williams, Edward Bennett -- Correspondence; Bank of Credit and Commerce International; Democratic Party (U.S.); United States. -- Department of Defense; United States; Banks and banking; Business